Allocation of special drawing rights for the first basic period : Proposal by the Managing Director. (International Monetary Fund, 1969)
The adequacy of international liquidity became a problem of increasing concern to the international community during the 1960's. In response, the IMF proposed a new facility, based on Special Drawing Rights, which took effect on October 3, 1969. This new facility, referred to in this publication, was established within the Fund as its Special Drawing Account, through which the new supplement to reserve assets, in the form of special drawing rights, could be allocated.